Benefit–risk evaluation of COVID-19 vaccination in special population groups of interest. Issue 32 (30th July 2022) - Moss, Paul; Berenbaum, Francis; Curigliano, Giuseppe; Grupper, Ayelet; Berg, Thomas; Pather, Shanti
Abstract: Several population groups display an increased risk of severe disease and mortality following SARS-CoV-2 infection. These include those who are immunocompromised (IC), have a cancer diagnosis, human immunodeficiency virus (HIV) infection or chronic inflammatory disease including autoimmune disease, primary immunodeficiencies, and those with kidney or liver disease. As such, improved understanding of the course of COVID-19 disease, as well as the efficacy, safety, and benefit-risk profiles of COVID-19 vaccines in these vulnerable groups is paramount in order to inform health policy makers and identify evidence-based vaccination strategies. In this review, we seek to summarize current data, including recommendations by national health authorities, on the impact and benefit-risk profiles of COVID-19 vaccination in these populations. Moving forward, although significant efforts have been made to elucidate and characterize COVID-19 disease course and vaccine responses in these groups, further larger-scale and longer-term evaluation will be instrumental to help further guide management and vaccination strategies, particularly given concerns about waning of vaccine-induced immunity and the recent surge of transmission with SARS-CoV-2 variants of concern.